Comparing Attitudes of Medical and Engineering Students in Karachi Towards Smoking - Nadia Jajja; Farah Ahmad; Syed Hasan Danish (ziauddin University, 2024)
In Pakistan, tobacco consumption is at an all-time high with the tobacco industry witnessing a boom. According to the Pakistan Tobacco Company, production and sale has taken a sharp leap from Rs.1,000 million rupees to Rs.1,750 million in 2008. The youth remain particularly vulnerable as massive antismoking ad campaigns have failed to drill in the health hazards. The aim of this study is to assess the attitude, perception and practices of youth regarding cigarette smoking. Comparative cross-sectional study was conducted in Ziauddin University and Bahria University. Sample was taken from all years of teaching. Data was collected through self-administered structured questionnaire that was developed in English. It comprised of questions pertaining to their year of study, smoking history, and perception and practices regarding smoking. A total of 450 students were surveyed, medicine (n=260) and engineering (n=190). One-fourth of the survey sample admitted to have tried to smoke at least once in their lifetime (p=0.001), and at least 20% medical students (n=53) and 35% of engineering students (n=66) surveyed had smoked a cigarette (p=0.001). While students studying medicine were better aware of the risks associated with smoking and tobacco consumption, however compared to engineering students their overall knowledge of the health risks was unsatisfactory. A significant number of medical students were unable to list and hence effectively counsel about long and short term health benefits. Peer pressure and media played a large role in students picking up the habit. KEY WORDS: Pakistan/Epidemiology, Smoking, Karachi, Mechanism Medical Students.